2022
DOI: 10.1111/imr.13074
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles and immune response during pregnancy: A balancing act*

Abstract: A healthy pregnancy represents an immunological paradox, first described by Peter Medawar, in which the fetus is not rejected by the maternal immune system. 1 Indeed, the feto-placental unit constitutes a semi-allogeneic graft within the maternal host, where typically maternal T and B lymphocytes have not been previously exposed to and tolerized by the expression of paternal antigens (Ags).The paradox is heightened when pregnancy results from a sperm and a donor oocyte, or in a surrogate pregnancy, where the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 255 publications
0
19
0
Order By: Relevance
“…Sun et al and Dr. Petroff, 7,11 as well as by Drs. Morelli and Sadovsky 12 who present a new mechanism of communication between the placenta and the maternal immune system.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al and Dr. Petroff, 7,11 as well as by Drs. Morelli and Sadovsky 12 who present a new mechanism of communication between the placenta and the maternal immune system.…”
Section: Figurementioning
confidence: 99%
“…and Dr. Petroff,7,11 as well as by Drs. Morelli and Sadovsky12 who present a new mechanism of communication between the placenta and the maternal immune system.An intriguing aspect of the immunology of pregnancy has been the role of immune cells at the implantation site, which represent a high percentage of the cell types of the endometrium and increase during early pregnancy. Dissecting their phenotype and their role has been an active area of research.A fundamental feature of the immune system is to protect the host from pathogens.…”
mentioning
confidence: 99%
“…With the advancement in scientific findings, new evidences suggested that immune checkpoint molecules and extracellular vesicles can mediate the maternal‐fetal crosstalk rendering coexistence of tolerance and nutrition in the interface 14,15 . In addition to these breakthrough discoveries, the regulatory roles of metabolic reprogramming in achieving appropriate immune adaption have also attracted extensive attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in scientific findings, new evidences suggested that immune checkpoint molecules and extracellular vesicles can mediate the maternal-fetal crosstalk rendering coexistence of tolerance and nutrition in the interface. 14,15 In addition to these breakthrough discoveries, the regulatory roles of metabolic reprogramming in achieving appropriate immune adaption have also attracted extensive attention in recent years. Besides being an importance of metabolic adaption during early pregnancy, aberrant metabolic profiling in systematic circulation and local maternalfetal interface was shown to be correlated with pregnancy loss and URPL.…”
mentioning
confidence: 99%
“…It is reasonably well established that the pre-implantation embryo communicates with the endometrium via EVs [10], whilst the early postimplantation embryo produces EVs that serve to dampen the maternal immune response and to remodel the maternal vascular system [11]. The placenta itself is a source of EVs and a number of recent reviews have discussed the role of these placental-derived EVs in mediating functions such as regulating maternal physiology, immune function and influencing the timing of birth [12][13][14][15][16][17][18]. Placental-derived EVs within maternal blood have been proposed as biomarkers for placenta-related diseases such as pre-eclampsia and gestational diabetes mellitus [17,19,20].…”
Section: Introductionmentioning
confidence: 99%